Determinação de resíduos de agrotóxicos em canola empregando método QuEChERS e UHPLC-MS/MS - Schreiber, Arthur Mateus (2022)
Rapeseed has been used as green fodder for animal feed, fertilizer for soil conditioning, and as a raw material for oil extraction. It has been used as human food, for industrial use, and more recently for the production of biofuel. The Brazilian production of canola has grown in the last two decades, the state of Rio Grande do Sul accounts for 98.7% of national production of the grain. In Brazil, there are about 20 pesticides registered for this crop. Currently, canola is not part of the foods monitored by the Pesticide Residue Analysis Program (PARA) of the National Health Surveillance Agency (ANVISA). Therefore, the development and application of analytical methods that allow the determination of pesticide residues of different classes in canola is important. Therefore, this research developed and validated an analytical method for the determination of 78 different pesticides in canola employing the QuEChERS method and ultra-high efficiency liquid chromatography coupled to serial mass spectrometry (UHPLC-MS/MS). The method was validated following the validation criteria established by SANTE (2021). The limit of quantification for most compounds was 10 μg kg-1 and the LOD was 3 μg kg-1. Most of the pesticides evaluated showed recoveries between 70 to 120% with RSD ≤20%. The proposed method was applied to 21 samples of canola grown in the state of Rio Grande do Sul. Of these, 11 samples presented pesticide residues, being 72.7% pesticides of not allowed use in Brazil for this crop. The fungicide trifloxystrobin presented a high concentration value (0.26 mg kg-1). The results obtained demonstrate that the proposed method is suitable for the determination of different classes of pesticides in canola.